Partikularität als Universalität: Zur Struktur von Psalm 72 - Bauer, Uwe F. W. (Biblische Notizen, 2024)
Emanuel Levinas makes it clear that the tension between particularity and universality is relevant in the Jewish tradition. This can also be seen in biblical texts such as Psalm 72, which can be understood uniformly in the sense of close reading. The various structural analyses of the psalm, which since Erich Zenger have resulted in a concentric structure, see the central theme of the psalm in vv. 8-11, i.e. in the universal reign of the king appointed by God. In contrast, my analysis, inspired by Frans Breukelman, shows a linear structure of the psalm. Vv. 2-7 focus on the reign of the earthly-idealised king for Israel and vv. 8-17 on his reign for all the nations of the earth. The final doxology summarises the sections vv. 2-7 and vv. 8-11 by calling for the blessing of the God of Israel (v. 18) as the God of the whole earth (v. 19) - a central aspect of biblical theology.